PUBLIC SERVICES THROUGH SP4N REPORT TO INCREASE EFFECTIVENESS AT THE MEDAN CITY DISKOMINFO - Dewi Sartika; Syafruddin Ritonga; Walid Musthafa Sembiring (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the implementation of public services through SP4N LAPOR at the Medan City Diskominfo in increasing the effectiveness of digital-based services. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, passive participatory observation, and documentation. Informants are selected purposively until data saturation is achieved. The analysis is carried out through data reduction, data presentation, and conclusion withdrawal and verification by triangulating sources and methods to ensure the validity of the findings. The results of the study show that the optimization of SP4N LAPOR is carried out through system integration with smart city platforms, strengthening technological infrastructure, standardizing response times, dashboard-based monitoring, and increasing apparatus capacity. Implementation is assessed based on the dimensions of tangible, reliability, responsiveness, assurance, and empathy. Supporting factors include ease of access and institutional commitment, while obstacles include inconsistency in responses between OPDs, network technical constraints, and uneven digital literacy of the community. SP4N LAPOR contributes to bureaucratic reform and participatory governance.